TinkerBell and the secret of the wings - Disney (Bath, England Parragon, 2012)
When Tinker Bell crosses the border into the mysterious Winter Woods, her wings begin to sparkle strangely. She is curious to find out why and she discovers a secret that will change her life and Pixie Hollow forever.